The Implementation of Productive Waqf in Pesantren: A Study of Unique Management Practices - triyawan, andi (Institut Agama Islam Negeri Kendari, 2023)
This paper discusses productive waqf and the uniqueness of the application of productive waqf management in a pesantren (Islamic boarding school). Furthermore, the standardization of the law used in the implementation of the productive waqf, which includes al-Qur'an, Hadits, fiqh rules, and aqwâl al-'ulamâ, must be examined in order to conclude the implementation status. There are many unique things to analyze in the implementation, such as the use of the institution fund, which is oriented to develop cash waqf, and the existence of the waqf board, which becomes the highest decision-maker. Because all of the pesantren's assets become waqf property, the highest leader is no longer on the foundation but on the waqf board.